Edible films and coatings from whey proteins: a review on formulation, and on mechanical and bioactive properties - Ramos, Óscar L. (2013)
The latest decade has witnessed joint efforts by the packaging and the food industries to reduce the amount of residues and wastes associated with food consumption. The recent increase in environmental awareness has also contributed toward development of edible packaging materials. Viable edible films and coatings have been successfully produced from whey proteins; their ability to serve other functions, viz. carrier of antimicrobials, antioxidants, or other nutraceuticals, without significantly compromising the desirable primary barrier and mechanical properties as packaging films, will add value for eventual commercial applications. These points are tackled in this review, in a critical manner. The supply of whey protein-based films and coatings, formulated to specifically address end-user needs, is also considered.